2023
DOI: 10.3389/fphar.2023.1156629
|View full text |Cite
|
Sign up to set email alerts
|

The role of RNA methyltransferase METTL3 in gynecologic cancers: Results and mechanisms

Abstract: N6-methyladenosine (m6A) methylation is the most prevalent mRNA modification in eukaryotes, and it is defined as the methylation of nitrogen atoms on the six adenine (A) bases of RNA in the presence of methyltransferases. Methyltransferase-like 3 (Mettl3), one of the components of m6A methyltransferase, plays a decisive catalytic role in m6A methylation. Recent studies have confirmed that m6A is associated with a wide spectrum of biological processes and it significantly affects disease progression and prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…METTL3 and METTL14 act as m6A regulators that can affect the progression of different human pathologies through oncogenic or suppressive methods. In several human cancers, for example, METTL3 plays an oncogenic role by upregulating oncogenes that support tumor progression 20 . Conversely, METTL3 also behaves as a suppressor in the central nervous system (CNS), for example, by upregulating tumor suppressor genes as well as genes that promote synaptic damage 21 .…”
Section: Importance/significance Of Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…METTL3 and METTL14 act as m6A regulators that can affect the progression of different human pathologies through oncogenic or suppressive methods. In several human cancers, for example, METTL3 plays an oncogenic role by upregulating oncogenes that support tumor progression 20 . Conversely, METTL3 also behaves as a suppressor in the central nervous system (CNS), for example, by upregulating tumor suppressor genes as well as genes that promote synaptic damage 21 .…”
Section: Importance/significance Of Methylationmentioning
confidence: 99%
“…In several human cancers, for example, METTL3 plays an oncogenic role by upregulating oncogenes that support tumor progression. 20 Conversely, METTL3 also behaves as a suppressor in the central nervous system (CNS), for example, by upregulating tumor suppressor genes as well as genes that promote synaptic damage. 21 These observations in the literature highlight the fact that METTL3-METTL14 are not globally uniform but rather, their roles in m6A modification produce specific downstream events based on the site of interest.…”
Section: Importance/significance Of Methylationmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] By regulating the m6A modification level of the target gene, METTL3 can affect the translation efficiency and post transcriptional modification of mRNA, thereby having a significant impact on cell function and physiological processes. 14,15 Research has shown that METTL3 is overexpressed in various tumours and is closely related to the biological behaviours of tumour cell proliferation, invasion and metastasis. [16][17][18][19][20][21][22] In previous studies, 23 we found that METTL3 is overexpressed in ESCA, and its expression level is closely related to 18 F-FDG PET/CT metabolic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…As a core component of m6A methylation, Methyltransferase 3 and N6‐Adenosine‐Methyltransferase Complex Catalytic Subunit (METTL3) is involved in the regulation of various biological processes, including cell proliferation, differentiation and metabolism 5–13 . By regulating the m6A modification level of the target gene, METTL3 can affect the translation efficiency and post transcriptional modification of mRNA, thereby having a significant impact on cell function and physiological processes 14,15 . Research has shown that METTL3 is overexpressed in various tumours and is closely related to the biological behaviours of tumour cell proliferation, invasion and metastasis 16–22 .…”
Section: Introductionmentioning
confidence: 99%